INVESTIGASI PERSEPSI CALON GURU MATEMATIKA TENTANG TPACK - Mutianingsih, Ninik; Prayitno, Lydia Lia; Chamidah, Amalia; Lestari, Dhea Ayu (TRANSFORMASI, 2023)
This pedagogical research discusses the technology used by prospective mathematics teachers at two private universities in Surabaya. 88 prospective mathematics teachers filled out the TPACK questionnaire and the data were analyzed descriptively using mean, standard deviation, and correlation test with the help of SPSS version 25. The results of this study showed that CK, PK, TK, and TPTCK simultaneously had an influence on the TPACK of prospective mathematics teachers at PGRI Adi Buana University Surabaya and Wijaya Kusuma University Surabaya. This is supported by the ANOVA test with result of sign = .000 < .05 so it can be said that the prospective mathematics teachers involved in this research have knowledge of all TPACK components. The results of this research recommend follow-up action to gain deeper insight into the implementation of TPACK for prospective teachers which is supported by existing infrastructure in the university environment as a means of learning prospective teachers as well as developing strategies for their mindset.